Peroralni antidiabetiki - pregled stanja in pogled v prihodnost - Zidar, Nace (Farmacevtski vestnik, 2019)
Type 2 diabetes mellitus is a chronic progressive metabolic disorder that occurs either when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. Because of their effectiveness and convenience of administration, oral antidiabetic drugs are frequently prescribed for the treatment of type 2 diabetes mellitus. Metformin and sulfonylureas are among the most known oral antidiabetic drugs and have been used in the clinic for more than 50 years. In addition, several other classes of drugs are known, such as meglitinides, thiazolidinediones, alpha-glucosidase inhibitors, dipeptidyl peptidase-4 (DPP-4) inhibitors and sodium/glucose cotransporter 2 (SGLT-2) inhibitors. The number of available therapies for the treatment of type 2 diabetes has grown considerably in recent years. In this paper, we present an overview of clinically approved oral antidiabetic agents and some new classes of drugs that are currently in different stages of development.
Keywords: metformin; peroralni antidiabetik; Sladkorna bolezen tip 2; sulfonilsečnina; zaviralec